The Impact of the Scale of Third-Party Logistics Guaranteeing Firms on Bank Credit Willingness in Supply Chain Finance: An ERP Study - Wang, Xuejiao; Zhao, Jie; Zhang, Hongjun; Tang, Xuelian (Frontiers in Psychology, 2022)
Supply chain financing guaranteed by third-party logistics (3PL) firms is an effective way to solve the financing difficulties of small and medium-sized enterprises (SMEs). Studies have explored factors that affect the willingness of supply chain financial credit providers under guarantee of 3PL firms (e.g., the scale of financing enterprises, credit). However, whether the scale of 3PL firms will affect the bank's credit decision has not been studied, as well as the neural processing of credit decisions. To clarify these issues, this study extracted behavioral and event-related potentials (ERPs) data when participants performed a selection task of judging whether to grant credit to guaranteed financing-seeking enterprises according to the large or small scale of the 3PL guaranteeing firms. The behavioral results showed that under the condition of a large-scale 3PL guaranteeing firm, the willingness to provide credit to SMEs was higher than that under the condition of a small-scale 3PL guaranteeing firm. This finding indicates there was credit scale discrimination against 3PL guaranteeing firms in supply chain finance. The ERP results showed that compared with the condition of a large-scale 3PL guaranteeing firm, a greater N2 amplitude was induced under the condition of a small-scale 3PL guaranteeing firm, which indicated that credit decision makers experienced greater perceived risk and more decision-making conflict. In contrast, a larger LPP amplitude was detected under the condition of a large-scale 3PL guaranteeing firm (as opposed to a small-scale firm), which indicated that large-scale 3PL guaranteeing firms received more positive comments and more positive emotions from credit decision-makers than small-scale 3PL guaranteeing firms. Based on these results, this study reveals the cognition process of credit decision makers regarding the impact of the 3PL guaranteeing firm scale on the willingness to provide credit in supply chain finance and explains the theory of credit scale discrimination from the perspective of decision neuroscience.